2020
DOI: 10.1161/atvbaha.119.313536
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Mediators, IL (Interleukin)-1β, TNF (Tumor Necrosis Factor) α, and Thrombin Directly Induce Capillary Tube Regression

Abstract: Objective: In this work, we examine the molecular basis for capillary tube regression and identify key proregressive factors, signaling pathways, and pharmacological antagonists of this process. Approach and Results: We demonstrate that the proinflammatory mediators, IL (interleukin)-1β, TNF (tumor necrosis factor) α, and thrombin, singly and in combination, are potent regulators of capillary tube regression in vitro. These proregressive factors, when a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 53 publications
3
61
1
Order By: Relevance
“…In a recent study, Koller and colleagues showed that proinflammatory mediators interleukin 1 β (IL1-β), TNF-α and thrombin can directly induce capillary tube regression of human umbilical vein ECs (HUVECs) in a 3D collagen regression assay [90]. In addition, prolonged inhibition of TNF-α reduced the severity of rarefaction, alleviated oxidative stress and decreased thromboxane A 2 production, whereas inhibition of thromboxane A 2 only blunted rarefaction.…”
Section: Soluble Factorsmentioning
confidence: 99%
“…In a recent study, Koller and colleagues showed that proinflammatory mediators interleukin 1 β (IL1-β), TNF-α and thrombin can directly induce capillary tube regression of human umbilical vein ECs (HUVECs) in a 3D collagen regression assay [90]. In addition, prolonged inhibition of TNF-α reduced the severity of rarefaction, alleviated oxidative stress and decreased thromboxane A 2 production, whereas inhibition of thromboxane A 2 only blunted rarefaction.…”
Section: Soluble Factorsmentioning
confidence: 99%
“…of the apical surface and collapse of EC-lined tube networks [11,51]. This occurs following addition of microtubule depolymerizing agents or the addition of the pro-regressive cytokines and proinflammatory mediators, IL-1β, TNFα and thrombin [11,51,52]. During capillary tube regression in response to these proinflammatory mediators, loss of acetylated tubulin was a key component of a capillary regression signaling signature that was identified [52].…”
Section: Plos Onementioning
confidence: 99%
“…This occurs following addition of microtubule depolymerizing agents or the addition of the pro-regressive cytokines and proinflammatory mediators, IL-1β, TNFα and thrombin [11,51,52]. During capillary tube regression in response to these proinflammatory mediators, loss of acetylated tubulin was a key component of a capillary regression signaling signature that was identified [52]. Thus, it appears that the microtubule cytoskeleton is necessary to support the formation of the apical membrane surface, but also to maintain its stability as EC-lined tubes mature.…”
Section: Plos Onementioning
confidence: 99%
“…These factors are interesting in the context of COVID-19-related vascular damage because of their known capacity to cause vascular permeability and/or thrombosis. They are also interesting to our two laboratories because of our recent work identifying key regulators of capillary regression [9]. Capillary regression (i.e.…”
Section: Communicationmentioning
confidence: 99%
“…EC loss and death) is an understudied process that appears to play a pathogenic role in numerous disease states, including hypertension, ischemia and infarction, diabetes, heart failure, malignant cancers, neurodegeneration, and sepsis. Our broad screen of many growth factors, cytokines and other molecules revealed that the most potent proregressive molecules we could identify were IL-1β, IL-1α, TNFα, and thrombin [9].…”
Section: Communicationmentioning
confidence: 99%